THE EFFECT OF TEACHER EDUCATION AND DISCIPLINE ON THE PERFORMANCE OF TEACHERS IN SMA NEGERI 2 MAJENE - Mariana, Lina (Jurnal Ekonomi Balance, 2019)
The Effect of Teacher Education and Work Discipline on Teacher Performance of  Majene 2 Senior High School. This study aims to determine whether Education has an effect on Teacher Performance in Majene 2 High School and to determine whether Work discipline influences Teacher Performance in Majene 2 Senior High School. The type of research data used is quantitative data using data analysis techniques. Data collection methods are used with questionnaire, interview and documentation techniques. This research was conducted for three months from January to March 2019. The results showed that there was no significant effect of education on the performance of the teachers of Majene 2 High School and there was a significant effect of work discipline on the performance of Majene 2 High School teachers.